(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article analyzes bioethical problems arising from the rapid development of artificial intelligence (AI) technologies in modern medicine. The use of AI tools in diagnostics, treatment, patient monitoring, and data management makes such issues as ethical responsibility for medical decisions, protection of personal data, and ensuring patient rights relevant. The research was conducted on the basis of international and national documents and practical experience. The article is aimed at identifying ways to ensure bioethical balance in the process of integrating AI technologies into the healthcare system.